Studies on resource and taxon of Osmanthusfagrans cultivars - HU Shao-qing; ZHANG Hou-yong; WU Guang-hong; XUAN Zi-can (浙江大学学报. 农业与生命科学版, 2005)
According to our miticulous observation and comparative study of of all the cultivars, the difference between Osmanthus fragrans var. subpaniculatus and Osmanthus fragrans is guite obvious of all the cultivars Sweet Osmanthus presently known. The affinity relationship between Osmanthus fragrans var. subpaniculatus and Sweet Osmanthus is analysed according to their morphylogical features, habits and their charcteristics on level of DNA and each taxon status is examined. A new taxon system of cultivars of Sweet Osmanthus is established.